Analisis Penataan Ulang (Benchmarking) Organisasi Komando Utama (Kotama) TNI AU - A. DIRWAN (JURNAL MITRA MANAJEMEN, 2013)
AbstractOrganization is a structured connection frame which contains privileges, responsibilities, and roles of work to do specific function. Organization theory is not only sees the achievement and attitude of the member, but also the organization ability as a whole to adapt and achieve the purposes. The Air Power organization which has the control of the air function, air strike, and air support, each need Unity of Command as its function. Besides, the Unity of Command concept at the air battle, the power cannot be divided, but must under Unified Commander to achieve the purpose. The Air Force of Operations Command, right now is an organization which the power usability is under command of Commander-in-Chief of TNI and to prepare is under Chief of Staff of Air Force. The roling function of Operations Command is based on Air Power doctrines, which still has the privileges duplication, and will break the flow of the operation. This paper will analyze those problems and give the alternative solution as suggestion to formulate the organization, especially divides to two Operations Commands, one has the Air Strike function, and another has Air Support function. Key Word : The Organization of Operations Command (Koops),Benchmarking, Air Power, Control of the Air, Air Strike, Air Support, Unity of Command, National of Air Defence Command (Kohanudnas) and Air Force Operations Command (Koopsau).